Chloroplastic ATP synthase builds up a proton motive force preventing production of reactive oxygen species in photosystem I. (23rd May 2017) - Takagi, Daisuke; Amako, Katsumi; Hashiguchi, Masaki; Fukaki, Hidehiro; Ishizaki, Kimitsune; Goh, Tatsuaki; Fukao, Yoichiro; Sano, Ryosuke; Kurata, Tetsuya; Demura, Taku; Sawa, Shinichiro; Miyake, Chikahiro
Summary: Over‐reduction of the photosynthetic electron transport (PET) chain should be avoided, because the accumulation of reducing electron carriers produces reactive oxygen species (ROS) within photosystem I (PSI) in thylakoid membranes and causes oxidative damage to chloroplasts. To prevent production of ROS in thylakoid membranes the H + gradient (ΔpH) needs to be built up across the thylakoid membranes to suppress the over‐reduction state of the PET chain. In this study, we aimed to identify the critical component that stimulates ΔpH formation under illumination in higher plants. To do this, we screened ethyl methane sulfonate (EMS)‐treated Arabidopsis thaliana, in which the formation of ΔpH is impaired and the PET chain caused over‐reduction under illumination. Subsequently, we isolated an allelic mutant that carries a missense mutation in the γ‐subunit of chloroplastic CF0 CF1 ‐ATP synthase, named hope2 . We found that hope2 suppressed the formation of ΔpH during photosynthesis because of the high H + efflux activity from the lumenal to stromal side of the thylakoid membranes via CF0 CF1 ‐ATP synthase. Furthermore, PSI was in a more reduced state in hope2 than in wild‐type (WT) plants, and hope2 was more vulnerable to PSI photoinhibition than WT under illumination. These results suggested that chloroplastic CF0 CF1 ‐ATP synthase adjusts the redox state of the PET chain, especially for PSI, by modulating H + efflux activity across the thylakoid membranes. Our findings suggest the importance of the buildup of ΔpH depending on CF0 CF1 ‐ATP synthase to adjust the redox state of the reaction center chlorophyll P700 in PSI and to suppress the production of ROS in PSI during photosynthesis. Significance Statement: ΔpH, as well as ATP supply, is important for the adjustment of the redox state in the photosynthetic electron transport chain in higher plants; however, how ΔpH formation is stimulated during photosynthesis is not yet known. This study aimed to identify the critical component to stimulate ΔpH formation during photosynthesis by using Arabidopsis thaliana mutagenized with ethyl methane sulfonate; chloroplastic CF0 CF1 ‐ATP synthase was found to build up ΔpH to protect photosynthetic machineries during photosynthesis.